Are profitable hospitals more digitally mature? An explorative study using data from the German DigitalRadar Project - Justus Vogel; Johannes Hollenbach; Alexander Haering; Boris Augurzky; Alexander Geissler (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
Public investment in hospitals in Germany has been insufficient for decades, making it difficultto finance digitization. Due to dual financing, hospitals could alternatively use their own profitsto pay for digitization efforts. This raises the question of whether there is a relationship betweenprofitability and digitization, i.e., whether profitable hospitals are more digitally mature, and whatother factors might influence digital maturity. To investigate this relationship, we use novel data ondigital maturity of German hospitals and combine them with balance sheet data. Our multivariateregression results do not show a robust correlation between profitability and digital maturity.Rather, being part of a large chain seems to be more important for digitalization. We concludethat hospitals in chains are more digitally mature because they benefit from a standardizationof IT infrastructure and internal policies. Individual hospitals may also benefit from centralizingparts of their IT strategy development. – – Die Finanzierung von Digitalisierungsprojekten in deutschen Krankenhäusern wird durch die seit Jahren zu geringen öffentlichen Investitionen erschwert. Aufgrund der dualen Finanzierung in Deutschland haben Krankenhäuser jedoch die Alternative, eigene Gewinne zur Finanzierung von Digitalisierungsmaßnahmen zu verwenden. Dies wirft die Frage auf, ob es einen Zusammenhang zwischen Profitabilität und Digitalisierungsgrad gibt, d.h. ob profitablere Krankenhäuser digital reifer sind und welche weiteren Faktoren die digitale Reife beeinflussen. Um diesen Zusammenhang zu untersuchen, verwenden wir neue Daten zum digitalen Reifegrad deutscher Krankenhäuser und kombinieren diese mit Bilanzdaten. Unsere multivariaten Regressionsergebnisse zeigen keinen robusten Zusammenhang zwischen Profitabilität und digitaler Reife. Vielmehr scheint die Zugehörigkeit zu einer großen Kette eine größere Bedeutung für die Digitalisierung zu haben. Größere Ketten sind digital reifer, weil sie eine kettenweite IT-Strategie verfolgen, die IT-Architektur und -Richtlinien standardisieren und Investitionen querfinanzieren können.
Keywords: I11; I18; M15; 330; Hospital profitability; hospital digitization; digital maturity